Effects of agmatine on the survival rate in rats bled to hemorrhage - GÜL, FETHİ; GÖREN, MEHMET ZAFER (Georg Thieme Verlag, 2011)
Agmatine (CAS 2482-00-0), an amine formed by decarboxylation of L-arginine, interacts with several targets like α2-adrenergic, imidazoline and N-methyl-Daspartic acid (NMDA) receptors and besides it is involved in the nitric oxide mediated effects. It has also been proposed that it possesses vasodilator effects and increases glomerular filtration rate in rats. The aim of this study was to supply evidence for the effects of agmatine in a rat model of hemorrhagic shock and explain the possible mechanisms of action. The iliac arteries and veins of Sprague-Dawley rats were catheterized under urethane anesthesia and around 2 ml/100 g blood was withdrawn within 20 min until the mean arterial blood pressure was stabilized around 25 mmHg. The rats were either pretreated with physiological saline, yohimbine (an α2- adrenergic receptor antagonist) or L-arginine (a nitric oxide donor) intravenously before administration of agmatine (300 μg/kg). Agmatine restored blood pressure in rats pretreated with physiological saline where all rats survived. Pretreatment with L-arginine abolished the increase in blood pressure produced by agmatine and the 1 h survival rate decreased to 67% (p < 0.01). Yohimbine pretreatment also suppressed agmatine induced restoration of blood pressure; however, the survival rate was found to be 17% for 3 min. No statistically significant effect was observed in the heart rate responses. These results may suggest that agmatine may increase survival through α2-adrenergic receptors and restores blood pressure through nitric oxide and adrenergic mechanisms in rats bled to hemorrhage. © ECV • Editio Cantor Verlag.
Keywords: Hemorrhagic shock; L-arginine; Nitric oxide (NO); Nitric oxide synthase inhibitor; Yohimbine